NEGOSIASI IDENTITAS DALAM REKONSILIASI KONFLIK ANTARETNIS (KASUS : RELASI ETNIS MADURA DENGAN ETNIS DAYAK) - Prathama, Nikolaus Ageng (Interaksi: Jurnal Ilmu Komunikasi, 2017)
ABSTRACTWhen a number of Madurese individual returned to the former conflict area in Central Kalimantan, the phenomena of identity negotiation in communication process between Dayaknese and Madurese individual has arisen. The events of social conflict between these two ethnic groups in 2001, tended to be a sensitive issue for Dayaknese and Madurese. Therefore, when Dayaknese and Madurese individual made contact and interact with each other, prejudice and negative stereotype were appeared. And then, mindful interethnics communication disturbed.The study based on genre of interpretive and phenomenology tradition, to get perceiver’s world, which is Dayaknese and Madurese individual, about identity negotiations in their daily interaction activities. Furthermore, by identity negotiation theory perspective, that accentuate mutual understanding among members of the dominant and minority groups, this study also seeks to gain meaning of individual relations of Dayaknese and Madurese ethnic which are understood by both parties in the framework of inter-ethnic conflict reconciliation.The results of this study indicate that relationships involving Dayak and Madura individuals in living together, have a positive development post social conflicts 2001. They could negotiated their own cultural identity in the process of daily interaction. However, there are still negative stereotypes, although their stereotypes do not completely block their intercultural interaction process. In addition, this study also revealed the results of the process of identity negotiation conducted by both parties. The form is the use of Dayaknese and Madurese Language and the existence of mixed marriages that are encouraged by both parties. The most prominent phenomenon in this Dayaknese and Madurese post-conflict individual relations is the cooperation made by the leaders to maintain good relations and prevent the emergence of social upheaval in the society.Key words: negotiations, reconciliations, conflict, Dayaknese, Madurese